Harmonious regulation flavor and lipid oxidation in dry-cured tenderloin through electrical stimulation: A study on lipase activity and sensory correlations - Lisha Lan; Li Chen; Xiaolin Zhong; Weiguo Cao; Ying Zhou; Jing Wan; Yuanyuan Liu; Qinjin Zhu (Food Chemistry: X)
This study examined the effects of electrical stimulation on dry-cured tenderloin at different processing stages (0, 4, and 11 days), with a primary focus on lipid oxidation and the composition of volatile compounds. The study's results revealed that electrical stimulation enhanced lipase activity and accelerated lipid oxidation. Compared to the control group, the electrically stimulated samples exhibited higher total amino acid and fatty acid contents. Furthermore, the electrically stimulated group demonstrated superior taste (as assessed by an electronic tongue) and aroma profiles (as assessed by an electronic nose). Among the 49 compounds identified by GC–MS, the electrically stimulated dry-cured tenderloin displayed a greater diversity of volatile compounds. Notably, certain compounds, including ethyl lactate, ethyl myristate, 2,3-octanedione, and cyclohexanone, were exclusively detected in the electrically stimulated samples. These findings offer novel insights into the interplay between lipid oxidation and flavor development during meat processing via electrical stimulation.